2022
DOI: 10.1002/ijc.34262
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Foxp3+ regulatory T cells but not the absence of CD19+IL‐10+ regulatory B cells hinders tumor growth in a para‐orthotopic neuroblastoma mouse model

Abstract: Adaptive immune cells with regulatory function reportedly mediate immune escape in a variety of tumors. Little is known regarding the relevance of the most prominent regulatory cell populations, namely Foxp3+ T regulatory cells (Tregs) and CD19+IL‐10+ B regulatory cells (Bregs), for neuroblastoma (NB) survival. After establishing a novel immunocompetent syngeneic NB mouse model where orthotopic tumors can be generated after intrarenal injection of NB975A cells, we studied the importance of Tregs and Bregs in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…However, administration of ULTRA-LEAF™ purified mAb depleted B cells, but did not suppress NB9464 tumor growth ( Figures S3A–C ). Taken together, these results suggest that macrophages and not B cells play an important role in the progression of NB, and these results were also validated by other groups ( 19 , 51 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, administration of ULTRA-LEAF™ purified mAb depleted B cells, but did not suppress NB9464 tumor growth ( Figures S3A–C ). Taken together, these results suggest that macrophages and not B cells play an important role in the progression of NB, and these results were also validated by other groups ( 19 , 51 ).…”
Section: Resultssupporting
confidence: 87%
“…The immune microenvironment of NB plays an important role in disease progression and predicting responses to immunotherapy (12,50). However, limited studies are available which exemplify the presence of immune cells in NB tumors (13,15,16).…”
Section: Resultsmentioning
confidence: 99%
“…Weißenborn et al created a cre‐flox mouse model for inducible deletion of IL‐10 on CD19 cells. However, Breg depletion did not show as significant of a tumor growth reduction in murine neuroblastoma as compared to Treg depletion 78 . Future work will be important to identify targetable cell‐surface markers to allow for selective Breg depletion.…”
Section: Developing Breg‐targeted Immunotherapiesmentioning
confidence: 89%
“…76 Matsushita et al describe using a monoclonal mouse antibody against CD22 that was shown to selectively deplete splenic B10 cells in an autoimmune encephalitis model, 77 Treg depletion. 78 Future work will be important to identify targetable cell-surface markers to allow for selective Breg depletion.…”
Section: Selective Depletion Of Bregs Has Been Technically Difficult ...mentioning
confidence: 99%